'Alternated Charting Statistic Modified Group Runs' (ACS‐MGR) control chart for monitoring mean vectors of bivariate and trivariate processes. (13th August 2020) - Gadre, Mukund P.; Venegurkar, Savita S.
Abstract: In this article, we propose "Alternated Charting Statistic‐Modified Group Runs" (ACS‐MGR) control chart for monitoring mean vectors of bivariate and trivariate processes, as an improvement over the ACS chart. This chart is obtained by combining ACS chart with the MGR chart, and it is verified that ACS‐MGR chart significantly reduces "Average Time to Signal" (ATS) as compared with ACS chart, when the process has gone out of control. Steady state performance of the chart is also studied by comparing with steady state performance of the ACS‐Syn chart and ACS‐GR chart.